Regulation of p53 activity in nuclear bodies by a specific PML isoform - Fogal, Valentina (Oxford University Press, 2000)
Covalent modification of the promyelocytic leukaemia protein (PML) by SUMO-1 is a prerequisite for the assembly of nuclear bodies (NBs), subnuclear structures disrupted in various human diseases and linked to transcriptional and growth control. Here we demonstrate that p53 is recruited into NBs by a specific PML isoform (PML3) or by coexpression of SUMO-1 and hUbc9. NB targeting depends on the direct association of p53, through its core domain, with a C-terminal region of PML3. The relocalization of p53 into NBs enhances p53 transactivation in a promoter-specific manner and affects cell survival. Our results indicate the existence of a cross-talk between PML- and p53-dependent growth suppression pathways, implying an important role for NBs and their resident proteins as modulators of p53 functions.